Analisis Pengaruh Ekspor Kopi, Tembakau, Dan Getah Karet Alam Terhadap Ekspor Di Sumatera Utara - Lia Nazliana Nasution; Mohammad Yusuf (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2018)
This study aims to determine the amount of coffee exported by  companies in North Sumatra, tobacco managed by regional companies and private companies managed in North Sumatra and to know the export of natural rubber latex carried out by companies in North Sumatra. The analysis method used is multiple linear regressionanalysis, with time series secondary data starting from 2001 to 2015. The independent variables used are coffee exports (X1), tobacco exports (X2), and exports of natural rubber latex (X3) while the dependent variable is Export (Y). The results obtained are: coffee export variables have a negative and significant effect on exports in North Sumatra, while the export variables of tobacco and naturalrubber sap exports have a positive and significant effect on exports in North Sumatra.